Amorphous silicon-based biological antibacterial composite board and preparation method thereof
Patent Information
- Application Number
- CN202611236868.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]此外,家居装饰墙面或台面容易因潮湿、油污或频繁接触而附着和滋生细菌、霉菌等微生物,因此除了具有良好的力学性能和尺寸稳定性外,还需要具备一定的抗菌性能;现有抗菌改性方法中,通常可将抗菌剂或负载型抗菌剂直接加入石英石板材中,如公开号为CN111875294A的专利申请文件,公开了一种抗菌防霉石英石及其制备方法,该申请文件通过添加磷酸锆载银锌复合抗菌剂能够在添加比例很低的情况下即可使石英石具有良好的抗菌效果和防霉效果,有助于节约成本,且不影响石英石的物理性能,然而该抗菌剂分散于石英石板材的整个基材内部,而板材的抗菌作用主要发生在其使用表面,包埋于板材内部的部分抗菌组分难以直接接触板材表面的微生物,其抗菌作用的发挥依赖于活性成分向表面的迁移,因而抗菌组分的有效利用率仍受到一定限制
本发明利用熔融石英砂、熔融石英粉与碳化硼颗粒的粒径级配填充基板孔隙,提高结构致密性;熔融石英骨料和碳化硼形成低膨胀、高刚性无机骨架,硅烷改性洋麻纤维在骨架与树脂胶结相之间发挥载荷传递和裂纹桥联作用。各组分协同作用,使基板具有良好的抗弯性能、抗冲击性能和热尺寸稳定性。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of engineered wood products technology, specifically to an amorphous silicon-based bio-antibacterial composite board and its preparation method. Background Technology
[0002] Quartz stone slabs are characterized by high hardness and good wear resistance, and are commonly used in home decoration such as walls, kitchen countertops, washbasins, coffee tables, dining tables, and windowsills. Most existing quartz stone slabs use natural crystalline quartz sand and quartz powder as the main aggregates. However, the thermal expansion characteristics of natural crystalline quartz aggregates differ from those of the organic resin binder. When the slab is used as a kitchen countertop and subjected to localized heating or alternating hot and cold temperatures from high-temperature appliances, uneven deformation and interfacial thermal stress can easily occur between the aggregates and the resin binder, affecting the dimensional stability and lifespan of the slab. Fused quartz sand is made from natural high-purity quartz or quartz sand, which is melted at high temperatures to transform the original crystalline silica structure into a molten state. After cooling, it forms an amorphous silica material, which is then crushed and sieved to obtain granular products. Compared to natural crystalline quartz, fused quartz has lower thermal expansion characteristics and better thermal shock resistance. Using it as aggregate in slabs helps improve the dimensional stability of the slabs under temperature changes.
[0003] In addition, home decoration walls or countertops are prone to the adhesion and growth of bacteria, mold and other microorganisms due to moisture, oil stains or frequent contact. Therefore, in addition to good mechanical properties and dimensional stability, they also need to have certain antibacterial properties. In existing antibacterial modification methods, antibacterial agents or loaded antibacterial agents can usually be directly added to quartz stone slabs. For example, patent application document with publication number CN111875294A discloses an antibacterial and anti-mildew quartz stone and its preparation method. This application document can give quartz stone good antibacterial and anti-mildew effects with a very low addition ratio by adding zirconium phosphate silver zinc composite antibacterial agent, which helps to save costs and does not affect the physical properties of quartz stone. However, the antibacterial agent is dispersed throughout the entire substrate of the quartz stone slab, while the antibacterial effect of the slab mainly occurs on its surface. The antibacterial components embedded in the slab are difficult to directly contact the microorganisms on the surface of the slab. The antibacterial effect depends on the migration of active ingredients to the surface. Therefore, the effective utilization rate of antibacterial components is still limited.
[0004] Therefore, there is a need to provide an amorphous silicon-based bio-antibacterial composite board and its preparation method to solve the above-mentioned technical problems. Summary of the Invention
[0005] In view of this, the present invention provides an amorphous silicon-based bio-antibacterial composite board and its preparation method, which can improve antibacterial performance while having good thermal dimensional stability and mechanical strength.
[0006] To achieve the above objectives, the present invention provides a method for preparing an amorphous silicon-based bio-antibacterial composite board, comprising the following steps:
[0007] S1. Deionized water, dispersant, bamboo leaf flavonoid-chitosan-coated peppermint oil microcapsules, water-based acrylate-modified polyurethane emulsion, and additives are mixed and allowed to stand to degas to obtain a bio-antibacterial coating. S2. Mix epoxy resin, boron carbide, dispersant, KH-560 and defoamer and degas under vacuum; then add silane-modified kenaf fiber, fused silica powder and fused silica sand in sequence, add curing agent, stir and degas under vacuum, pour into mold, and after vacuum vibration, pre-pressing and staged heating and pressure curing, cool and demold, then after post-curing, curing, edge trimming, polishing, cleaning and drying, to obtain an amorphous silicon substrate. S3. Apply the bio-antibacterial coating to the surface of an amorphous silicon substrate. After spraying, level, dry, cool and cure to obtain an amorphous silicon-based bio-antibacterial composite board.
[0008] This invention uses fused silica sand and fused silica powder as amorphous silicon-based aggregates. Utilizing the particle size distribution between the fused silica sand, fused silica powder, and boron carbide particles, fine particles fill the gaps between the fused silica sand particles, reducing internal porosity of the substrate, improving structural density, and thus enhancing overall strength. The fused silica aggregate and boron carbide particles together form a low-expansion, high-rigidity inorganic framework. Silane-modified kenaf fibers are distributed between the framework and the resin binder phase. These three components synergistically constrain thermal deformation and disperse internal stresses caused by temperature changes, thereby reducing the risk of warping, cracking, and dimensional changes. Simultaneously, the fused silica aggregate and boron carbide particles increase the stiffness of the composite system and share bending loads, while the kenaf fibers delay crack propagation through load transfer and crack bridging. Thus, the synergistic effect of these components results in an amorphous silicon-based substrate with high density, excellent bending resistance, impact resistance, and thermal stability.
[0009] This invention utilizes bamboo leaf flavonoids-chitosan-encapsulated peppermint oil microcapsules as a biological antibacterial component. The active ingredients in peppermint oil inhibit microorganisms adhering to the surface of the substrate; chitosan possesses antibacterial and film-forming properties and can serve as the microcapsule wall material to encapsulate the peppermint oil, reducing its rapid volatilization during coating preparation and use; bamboo leaf flavonoids contain polyphenolic active ingredients, which interact with chitosan through hydrogen bonds to form a composite wall layer, exerting antibacterial and antioxidant effects, thus maintaining the stability of the microcapsule wall layer and the active ingredients of the peppermint oil. After the microcapsules are dispersed in an aqueous acrylate-modified polyurethane coating, the film-forming emulsion fixes and protects the microcapsules, reducing the risk of detachment and breakage, while allowing the active ingredients of the peppermint oil to be gradually released, improving the durability of the antibacterial effect and imparting a distinctive peppermint oil aroma to the substrate surface.
[0010] Optionally, the bamboo leaf flavonoid-chitosan-coated peppermint oil microcapsules consist of 5-5.5 parts peppermint oil and 5-5.5 parts Tween Mix 80 parts and add dropwise to 125-130 parts of deionized water under continuous stirring at 45-50℃ and 1000-1200r / min. After the addition is complete, continue emulsification for 30-45min. Place in a water bath at 45-50℃ and add bamboo leaf flavonoid-chitosan composite solution dropwise under continuous stirring at 1000r / min. After the addition is complete, adjust the pH of the system to 3.8-4.2 with 10wt% citric acid monohydrate aqueous solution and react for 60-80min. Then add 30-50 parts of 2wt% sodium tripolyphosphate aqueous solution and continue the reaction for 60-70min. After cooling to room temperature and standing for 60-70min, spray dry under the conditions of feed rate of 100-120mL / h and air inlet temperature of 120℃. Collect the obtained powder, cool, lightly grind and pass through a 150-mesh sieve.
[0011] Tween 80 reduces the interfacial tension between oil and water, allowing peppermint essential oil to form stable, fine droplets; under acidic conditions of pH 3.8–4.2, the amino groups on the chitosan molecular chains are protonated to form -NH3. + The process involves adsorbing and coating chitosan onto the surface of essential oil droplets, while bamboo leaf flavonoids bind to chitosan through hydrogen bonds and hydrophobic interactions, forming a composite wall layer. The addition of sodium tripolyphosphate causes electrostatic interactions and ionic cross-linking between its polyphosphate groups and the protonated amino groups of chitosan, further solidifying the wall layer and forming a stable three-dimensional network structure. After rapid dehydration via spray drying, the composite wall material solidifies on the surface of the essential oil droplets, ultimately forming microcapsules with peppermint essential oil as the core material and a bamboo leaf flavonoid-chitosan cross-linked layer as the wall material. This reduces essential oil volatilization and oxidation loss and facilitates its slow release.
[0012] Optionally, the bamboo leaf flavonoid-chitosan composite solution is prepared by the following method: 1.25-1.45 parts of bamboo leaf flavonoids are added to 85-95 parts of deionized water and stirred at 45-50°C for 10-15 minutes, then slowly added dropwise to the chitosan solution, and stirring is continued for 20-30 minutes after the addition is completed; the chitosan solution is obtained by adding 3.8-4.2 parts of chitosan to 350-400 parts of 1wt% acetic acid aqueous solution and stirring at 50°C for 1-2 hours.
[0013] Optionally, in step S1, 4.5-5 parts of deionized water and 0.1-0.2 parts of dispersant are mixed and stirred for 3-5 minutes. Then, 3-5 parts of bamboo leaf flavonoid-chitosan-coated peppermint oil microcapsules are added in 2-3 portions and stirred for 10-15 minutes. Next, 87-92 parts of waterborne acrylate-modified polyurethane emulsion are added and stirred for 15-20 minutes. Then, additives are added and stirring is continued for 5-8 minutes. The mixture is allowed to stand and defoam to obtain a bio-antibacterial coating. The additives include 0.2-0.22 parts of leveling agent and 0.2-0.22 parts of waterborne defoamer.
[0014] Optionally, the silane-modified kenaf fiber is obtained by adding 1.2-1.6 parts of KH-560 to 280-320 parts of 95 vol% ethanol aqueous solution, adjusting the pH to 4.5-5.0 with glacial acetic acid, stirring and pre-hydrolyzing for 30-40 min, adding 30-32 parts of alkali to treat the kenaf fiber for impregnation for 30-40 min, and vacuum drying at 70-80℃ for 4-6 h.
[0015] Under weakly acidic conditions, the silanol groups formed by the pre-hydrolysis of KH-560 can react with the hydroxyl groups on the surface of kenaf fibers, and their epoxy groups can participate in the epoxy resin curing reaction, thereby enhancing the interfacial bonding between kenaf fibers and the resin cementing phase. This modification helps improve the wettability and dispersibility of fibers in the resin system, reduces fiber agglomeration and interfacial debonding, improves load transfer efficiency, and allows kenaf fibers to better perform their reinforcing and crack bridging functions.
[0016] Optionally, the alkali-treated kenaf fiber is obtained by cutting 35-40 parts of kenaf fiber to a length of 8-12 mm, immersing it in 640-680 parts of a 5% sodium hydroxide aqueous solution for 60-80 min, washing it with deionized water 4-6 times, and vacuum drying it at 70-80℃ for 8-10 h.
[0017] Alkali treatment can remove some of the lignin, hemicellulose and impurities from the surface of kenaf fibers, roughening the fiber surface and exposing more hydroxyl groups, which is beneficial for subsequent silane coupling agent modification.
[0018] Optionally, in step S2, the first part of epoxy resin, boron carbide, and dispersant are mixed and dispersed at high speed at 1000-1200 r / min for 20-30 min. Then, the remaining epoxy resin, KH-560, and defoamer are added and mixed for 12-16 min. Vacuum degassing is performed at -0.08 MPa for 8-10 min. Silane-modified kenaf fiber is added in 2-3 portions and mixed for 5-8 min. Then, fused silica powder and fused silica sand are added sequentially and mixed for 10-12 min. Finally, the curing agent is added and mixed for 2 minutes. ~4min, vacuum degassing at -0.08MPa for 3~4min, then spread into a mold, vibrate under -0.08MPa vacuum for 5~6min, then pre-press at 2.5MPa for 12~15min, hold pressure and cure at 60~65℃ for 60~70min, then hold pressure and cure at 75~80℃ for 90~120min, cool, depressurize, demold, and post-cur at 90~100℃ for 2~3h. After curing, trimming, polishing, dust removal, washing with anhydrous ethanol and drying, an amorphous silicon substrate is obtained.
[0019] Optionally, the amount of the first part of epoxy resin is 60-70 parts, and the amount of the remaining epoxy resin is 115-125 parts; the sanding is done with 400-grit and 600-grit sandpaper; the defoamer is specifically an organosilicon defoamer.
[0020] The epoxy resin is added in two stages. First, a small amount of resin forms a concentrated dispersion system with high shear, promoting boron carbide wetting and depolymerization. Then, the remaining resin is added to adjust the system viscosity, facilitating the uniform mixing of subsequent fibers and quartz aggregates. Sanding with 400-grit and 600-grit sandpaper sequentially removes surface protrusions and molding defects, refines sanding scratches, and improves surface smoothness and cleanliness. This promotes uniform spreading of the antibacterial coating and enhances its adhesion to the substrate.
[0021] Preferably, the epoxy resin is a bisphenol A type liquid epoxy resin.
[0022] Optionally, in step S3, the bio-antibacterial coating is sprayed onto the surface of the amorphous silicon substrate, with the spraying pressure controlled at 0.20~0.30MPa, the distance between the spray gun and the substrate surface at 15~20cm, and the coating amount at 150~170g / m². 2 After spraying, level at 25~27℃ for 20~30 min, pre-dry at 45~50℃ for 20~30 min, then dry at 55~60℃ for 30~40 min, and after cooling, cure at room temperature for 36~48 h to obtain amorphous silicon-based bio-antibacterial composite board.
[0023] This invention also provides an amorphous silicon-based bio-antibacterial composite board, prepared by the above-described method, comprising an amorphous silicon substrate and a bio-antibacterial coating sprayed onto the surface of the amorphous silicon substrate; the amorphous silicon substrate comprises the following raw materials in parts by weight: 175-195 parts epoxy resin, 20-25 parts boron carbide, 1.2-1.6 parts dispersant, 4-5 parts KH-560, 0.4-0.6 parts defoamer, 28-32 parts silane-modified kenaf fiber, 150-160 parts fused silica powder, 640-650 parts fused silica sand, and 20-22 parts curing agent; the thickness of the amorphous silicon substrate is 14.5-15.5 mm, and the dry film thickness of the bio-antibacterial coating is 50-70 μm.
[0024] The above component ratio allows the epoxy resin to fully bond the fused silica aggregate, and the boron carbide and silane-modified kenaf fibers achieve both particle and fiber reinforcement. KH-560 helps improve the interfacial bonding of each phase, thus balancing the substrate's density, flexural strength, and impact resistance. Controlling the dry film thickness of the antibacterial coating to 50~70μm ensures sufficient surface loading of the antibacterial components and coating continuity, while avoiding uneven drying or cracking caused by excessive coating thickness.
[0025] The above-described technical solution of the present invention has at least the following beneficial effects: This invention utilizes the particle size distribution of fused silica sand, fused silica powder, and boron carbide particles to fill the pores of the substrate, improving structural density. The fused silica aggregate and boron carbide form a low-expansion, high-rigidity inorganic skeleton, while silane-modified kenaf fibers play a role in load transfer and crack bridging between the skeleton and the resin cementing phase. The synergistic effect of these components gives the substrate excellent bending resistance, impact resistance, and thermal dimensional stability.
[0026] This invention utilizes bamboo leaf flavonoids-chitosan-encapsulated peppermint essential oil microcapsules as a biological antibacterial component. Peppermint essential oil provides antibacterial activity, while chitosan possesses both antibacterial and film-forming properties, encapsulating the essential oil and reducing its volatilization. Bamboo leaf flavonoids enhance the stability of the composite wall layer and delay the oxidative loss of active ingredients. After the microcapsules are dispersed in an aqueous acrylate-modified polyurethane coating, they are immobilized and protected, gradually releasing the active ingredients of peppermint essential oil, thereby improving the durability of the antibacterial effect and imparting a distinctive peppermint essential oil odor to the surface of the substrate. Detailed Implementation
[0027] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. The described embodiments are some embodiments of the present invention, and all other embodiments obtained by those skilled in the art based on the described embodiments of the present invention are within the scope of protection of the present invention.
[0028] Example 1 Four parts of chitosan were added to 375 parts of 1 wt% acetic acid aqueous solution and stirred at 50℃ for 1.5 h to obtain a chitosan solution. 1.35 parts of bamboo leaf flavonoids were added to 90 parts of deionized water and stirred at 48℃ for 12 min. Then, the solution was slowly added dropwise to the chitosan solution. After the addition was completed, the solution was stirred for another 25 min to obtain a bamboo leaf flavonoid-chitosan composite solution.
[0029] 5.25 parts of peppermint essential oil and 5.25 parts of Tween 80 were mixed and added dropwise to 128 parts of deionized water under continuous stirring at 1100 r / min and 48℃. After the addition was completed, emulsification was continued for 40 min. The mixture was placed in a 48℃ water bath and bamboo leaf flavonoid-chitosan composite solution was added dropwise under continuous stirring at 1000 r / min. After the addition was completed, the pH of the system was adjusted to 4.0 with 10 wt% citric acid monohydrate aqueous solution and the reaction was carried out for 70 min. Then, 40 parts of 2 wt% sodium tripolyphosphate aqueous solution were added and the reaction was continued for 65 min. After cooling to room temperature and standing for 65 min, the mixture was spray-dried under the conditions of feed rate of 110 mL / h and air inlet temperature of 120℃. The resulting powder was collected, cooled, lightly dispersed and passed through a 150 mesh sieve to obtain bamboo leaf flavonoid-chitosan-coated peppermint essential oil microcapsules.
[0030] Mix 4.8 parts of deionized water with 0.15 parts of dispersant (model: DISPERBYK-190) and stir for 4 minutes. Add 4 parts of bamboo leaf flavonoid-chitosan-coated peppermint oil microcapsules in 3 portions and stir for 12 minutes each time. Add 90 parts of waterborne acrylate-modified polyurethane emulsion (model: EV-6154, solid content 40%±0.5%) and stir for 18 minutes. Then add 0.21 parts of leveling agent (model: BYK-348) and 0.21 parts of waterborne defoamer (model: BYK-024) in sequence and continue stirring for 6 minutes. Allow to stand to defoam and obtain the bio-antibacterial coating.
[0031] 38 parts of kenaf fiber were cut to a length of 10 mm and then immersed in 660 parts of a 5% sodium hydroxide aqueous solution for 70 min. After washing with deionized water 5 times, the kenaf fiber was vacuum dried at 75 °C for 9 h to obtain alkali-treated kenaf fiber. 1.4 parts of KH-560 were added to 300 parts of a 95 vol% ethanol aqueous solution, the pH was adjusted to 4.8 with glacial acetic acid, and the mixture was stirred and pre-hydrolyzed for 35 min. 31 parts of alkali-treated kenaf fiber were then added and immersed for 35 min. The kenaf fiber was then vacuum dried at 75 °C for 5 h to obtain silane-modified kenaf fiber.
[0032] 65 parts of bisphenol A type liquid epoxy resin (model: CYD-128), 23 parts of boron carbide (average particle size 9±2μm), and 1.4 parts of dispersant (model: BYK-W 9010) were mixed and dispersed at 1100 r / min for 25 min. Then, 120 parts of bisphenol A type liquid epoxy resin, 4.5 parts of KH-560, and 0.5 parts of silicone defoamer (model: BYK-088) were added and stirred for 14 min. Vacuum degassing was carried out at -0.08 MPa for 9 min. 30 parts of silane-modified kenaf fiber were added in three batches and stirred for 7 min each time. Then, 155 parts of fused silica powder (particle size ≤45μm) and 645 parts of fused silica sand (20~80 mesh) were added and stirred for 11 min each time. Add 21 parts of curing agent (model: HY951) and stir for 3 minutes. Degas under vacuum at -0.08 MPa for 4 minutes. Pour into a mold and vibrate under vacuum at -0.08 MPa for 5 minutes. Pre-press at 2.5 MPa for 13 minutes. Hold pressure and cure at 63℃ for 65 minutes. Hold pressure and cure at 78℃ for 105 minutes. Cool, release pressure, demold, and post-cur at 95℃ for 2.5 hours. After curing, trim the edges, polish with 400-grit and 600-grit sandpaper, remove dust, wash with anhydrous ethanol, and dry to obtain an amorphous silicon substrate.
[0033] The bio-antibacterial coating was sprayed onto the surface of an amorphous silicon substrate. The spraying pressure was controlled at 0.25 MPa, the distance between the spray gun and the substrate surface was 18 cm, and the coating amount was 160 g / m². After spraying, the coating was leveled at 26 °C for 25 min, pre-dried at 48 °C for 25 min, and then dried at 58 °C for 35 min. After cooling, the coating was cured at room temperature for 42 h to obtain an amorphous silicon-based bio-antibacterial composite board (the dry film thickness of the bio-antibacterial coating was 60 μm).
[0034] Example 2 3.8 parts of chitosan were added to 350 parts of 1 wt% acetic acid aqueous solution and stirred at 50℃ for 1 h to obtain chitosan solution; 1.25 parts of bamboo leaf flavonoids were added to 85 parts of deionized water and stirred at 45℃ for 10 min, and then slowly added dropwise to chitosan solution. After the addition was completed, stirring was continued for 20 min to obtain bamboo leaf flavonoid-chitosan composite solution.
[0035] Five parts of peppermint essential oil and five parts of Tween 80 were mixed and added dropwise to 125 parts of deionized water under continuous stirring at 1000 rpm at 45°C. After the addition was completed, emulsification was continued for 30 min. The mixture was then placed in a 45°C water bath and a bamboo leaf flavonoid-chitosan composite solution was added dropwise under continuous stirring at 1000 rpm. After the addition was completed, the pH of the system was adjusted to 3.8 with a 10 wt% citric acid monohydrate aqueous solution and the reaction was carried out for 60 min. Subsequently, 30 parts of 2 wt% sodium tripolyphosphate aqueous solution were added and the reaction was continued for 60 min. After cooling to room temperature and standing for 60 min, the mixture was spray-dried under conditions of a feed rate of 100 mL / h and an air inlet temperature of 120°C. The resulting powder was collected, cooled, lightly dispersed, and passed through a 150-mesh sieve to obtain bamboo leaf flavonoid-chitosan-coated peppermint essential oil microcapsules.
[0036] Mix 4.5 parts of deionized water with 0.1 parts of dispersant (model: DISPERBYK-190) and stir for 3 minutes. Add 3 parts of bamboo leaf flavonoid-chitosan-coated peppermint oil microcapsules in two batches and stir for 10 minutes each time. Add 87 parts of waterborne acrylic ester modified polyurethane emulsion (model: EV-6154, solid content 40%±0.5%) and stir for 15 minutes. Then add 0.2 parts of leveling agent (model: BYK-348) and 0.2 parts of waterborne defoamer (model: BYK-024) in sequence and continue stirring for 5 minutes. Let stand to defoam and obtain the bio-antibacterial coating.
[0037] 35 parts of kenaf fiber were cut to a length of 8 mm and then immersed in 640 parts of a 5% sodium hydroxide aqueous solution for 60 min. After washing with deionized water four times, the kenaf fiber was vacuum dried at 70 °C for 8 h to obtain alkali-treated kenaf fiber. 1.2 parts of KH-560 were added to 280 parts of a 95 vol% ethanol aqueous solution, the pH was adjusted to 4.5 with glacial acetic acid, and the mixture was stirred and pre-hydrolyzed for 30 min. 30 parts of alkali-treated kenaf fiber were then added and immersed for 30 min. After vacuum drying at 70 °C for 4 h, silane-modified kenaf fiber was obtained.
[0038] Mix 60 parts of bisphenol A type liquid epoxy resin (model: CYD-128), 20 parts of boron carbide (average particle size 9±2μm), and 1.2 parts of dispersant (model: BYK-W 9010), and disperse at 1000 r / min for 20 min. Then add 115 parts of bisphenol A type liquid epoxy resin, 4 parts of KH-560, and 0.4 parts of silicone defoamer (model: BYK-088), and stir for 12 min. Degas under vacuum at -0.08 MPa for 8 min. Add 28 parts of silane-modified kenaf fiber in two batches, and stir for 5 min each time. Then add 150 parts of fused silica powder (particle size ≤45μm) and 640 parts of fused silica sand (20~80 mesh), and stir for 10 min each time. Add 20 parts of curing agent (model: HY951) and stir for 2 minutes. Degas under vacuum at -0.08 MPa for 3 minutes. Pour into a mold and vibrate under vacuum at -0.08 MPa for 5 minutes. Then pre-press at 2.5 MPa for 12 minutes. Hold pressure and cure at 60℃ for 60 minutes. Then hold pressure and cure at 75℃ for 90 minutes. Cool, release pressure, demold, and post-cur at 90℃ for 2 hours. After curing, trim the edges, polish with 400-grit and 600-grit sandpaper, remove dust, wash with anhydrous ethanol and dry to obtain an amorphous silicon substrate.
[0039] The bio-antibacterial coating was sprayed onto the surface of an amorphous silicon substrate. The spraying pressure was controlled at 0.20 MPa, the distance between the spray gun and the substrate surface was 15 cm, and the coating amount was 150 g / m². After spraying, the coating was leveled at 25 °C for 20 min, pre-dried at 45 °C for 20 min, and then dried at 55 °C for 30 min. After cooling, the coating was cured at room temperature for 36 h to obtain an amorphous silicon-based bio-antibacterial composite board (the dry film thickness of the bio-antibacterial coating was 50 μm).
[0040] Example 3 4.2 parts of chitosan were added to 400 parts of 1 wt% acetic acid aqueous solution and stirred at 50℃ for 2 h to obtain chitosan solution; 1.45 parts of bamboo leaf flavonoids were added to 95 parts of deionized water and stirred at 50℃ for 15 min, and then slowly added dropwise to chitosan solution. After the addition was completed, stirring was continued for 30 min to obtain bamboo leaf flavonoid-chitosan composite solution.
[0041] 5.5 parts of peppermint essential oil and 5.5 parts of Tween 80 were mixed and added dropwise to 130 parts of deionized water under continuous stirring at 1200 r / min and 50℃. After the addition was completed, emulsification was continued for 45 min. The mixture was placed in a 50℃ water bath and bamboo leaf flavonoid-chitosan composite solution was added dropwise under continuous stirring at 1000 r / min. After the addition was completed, the pH of the system was adjusted to 4.2 with 10 wt% citric acid monohydrate aqueous solution and the reaction was carried out for 80 min. Then, 50 parts of 2 wt% sodium tripolyphosphate aqueous solution were added and the reaction was continued for 70 min. After cooling to room temperature and standing for 70 min, the mixture was spray-dried under the conditions of feed rate of 120 mL / h and air inlet temperature of 120℃. The resulting powder was collected, cooled, lightly dispersed and passed through a 150 mesh sieve to obtain bamboo leaf flavonoid-chitosan-coated peppermint essential oil microcapsules.
[0042] Mix 5 parts of deionized water with 0.2 parts of dispersant (model: DISPERBYK-190) and stir for 5 minutes. Add 5 parts of bamboo leaf flavonoid-chitosan-coated peppermint oil microcapsules in 3 portions and stir for 15 minutes each time. Add 92 parts of waterborne acrylate-modified polyurethane emulsion (model: EV-6154, solid content 40%±0.5%) and stir for 20 minutes. Then add 0.22 parts of leveling agent (model: BYK-348) and 0.22 parts of waterborne defoamer (model: BYK-024) in sequence and continue stirring for 8 minutes. Allow to stand to defoam and obtain the bio-antibacterial coating.
[0043] Forty parts of kenaf fiber were cut to a length of 12 mm and then immersed in 680 parts of a 5% sodium hydroxide aqueous solution for 80 min. After washing with deionized water 6 times, the kenaf fiber was vacuum dried at 80 °C for 10 h to obtain alkali-treated kenaf fiber. 1.6 parts of KH-560 were added to 320 parts of a 95 vol% ethanol aqueous solution, the pH was adjusted to 5.0 with glacial acetic acid, and the mixture was stirred and pre-hydrolyzed for 40 min. Then, 32 parts of alkali-treated kenaf fiber were added and immersed for 40 min. Finally, the kenaf fiber was vacuum dried at 80 °C for 6 h to obtain silane-modified kenaf fiber.
[0044] 70 parts of bisphenol A type liquid epoxy resin (model: CYD-128), 25 parts of boron carbide (average particle size 9±2μm), and 1.6 parts of dispersant (model: BYK-W 9010) were mixed and dispersed at 1200 r / min for 30 min. Then, 125 parts of bisphenol A type liquid epoxy resin, 5 parts of KH-560, and 0.6 parts of silicone defoamer (model: BYK-088) were added and stirred for 16 min. Vacuum degassing was performed at -0.08 MPa for 10 min. 32 parts of silane-modified kenaf fiber were added in three batches and stirred for 8 min each time. Then, 160 parts of fused silica powder (particle size ≤45μm) and 650 parts of fused silica sand (20~80 mesh) were added and stirred for 12 min each time. 22 parts of curing agent (model: HY951) were stirred for 4 min, vacuum degassed at -0.08 MPa for 4 min, poured into a mold, vibrated under vacuum of -0.08 MPa for 6 min, pre-pressed at 2.5 MPa for 15 min, held at 65℃ for 70 min, and then held at 80℃ for 120 min. After cooling, depressurization, and demolding, the substrate was post-cured at 100℃ for 3 h. After curing, edge trimming, sanding with 400 grit and 600 grit sandpaper, dust removal, washing with anhydrous ethanol, and drying, an amorphous silicon substrate was obtained.
[0045] The bio-antibacterial coating was sprayed onto the surface of an amorphous silicon substrate. The spraying pressure was controlled at 0.30 MPa, the distance between the spray gun and the substrate surface was 20 cm, and the coating amount was 170 g / m². After spraying, the coating was leveled at 27 °C for 30 min, pre-dried at 50 °C for 30 min, and then dried at 60 °C for 40 min. After cooling, the coating was cured at room temperature for 48 h to obtain an amorphous silicon-based bio-antibacterial composite board (the dry film thickness of the bio-antibacterial coating was 70 μm).
[0046] Example 4 3.9 parts of chitosan were added to 365 parts of 1wt% acetic acid aqueous solution and stirred at 50℃ for 1.2h to obtain chitosan solution; 1.30 parts of bamboo leaf flavonoids were added to 88 parts of deionized water and stirred at 46℃ for 12min, and then slowly added dropwise to chitosan solution. After the addition was completed, stirring was continued for 22min to obtain bamboo leaf flavonoid-chitosan composite solution.
[0047] 5.1 parts of peppermint essential oil and 5.1 parts of Tween 80 were mixed and added dropwise to 126 parts of deionized water under continuous stirring at 1050 r / min and 46℃. After the addition was completed, emulsification was continued for 35 min. The mixture was placed in a 46℃ water bath and bamboo leaf flavonoid-chitosan composite solution was added dropwise under continuous stirring at 1000 r / min. After the addition was completed, the pH of the system was adjusted to 3.9 with 10 wt% citric acid monohydrate aqueous solution and the reaction was carried out for 65 min. Then, 35 parts of 2 wt% sodium tripolyphosphate aqueous solution were added and the reaction was continued for 62 min. After cooling to room temperature and standing for 62 min, the mixture was spray-dried under the conditions of feed rate of 105 mL / h and air inlet temperature of 120℃. The resulting powder was collected, cooled, lightly dispersed and passed through a 150 mesh sieve to obtain bamboo leaf flavonoid-chitosan-coated peppermint essential oil microcapsules.
[0048] Mix 4.6 parts of deionized water with 0.12 parts of dispersant (model: DISPERBYK-190) and stir for 4 minutes. Add 3.5 parts of bamboo leaf flavonoid-chitosan-coated peppermint oil microcapsules in two batches and stir for 11 minutes. Add 88.5 parts of waterborne acrylate-modified polyurethane emulsion (model: EV-6154, solid content 40%±0.5%) and stir for 16 minutes. Then add 0.21 parts of leveling agent (model: BYK-348) and 0.20 parts of waterborne defoamer (model: BYK-024) and continue stirring for 6 minutes. Let stand to defoam and obtain the bio-antibacterial coating.
[0049] Thirty-six parts of kenaf fiber were cut to a length of 9 mm and then immersed in 650 parts of a 5% sodium hydroxide aqueous solution for 65 min. After washing with deionized water five times, the kenaf fiber was vacuum dried at 72 °C for 8.5 h to obtain alkali-treated kenaf fiber. One-third of KH-560 was added to 290 parts of a 95 vol% ethanol aqueous solution, the pH was adjusted to 4.6 with glacial acetic acid, and the mixture was stirred and pre-hydrolyzed for 32 min. Thirty-one parts of alkali-treated kenaf fiber were then added and immersed for 32 min. The kenaf fiber was then vacuum dried at 72 °C for 4.5 h to obtain silane-modified kenaf fiber.
[0050] 62 parts of bisphenol A type liquid epoxy resin (model: CYD-128), 21 parts of boron carbide (average particle size 9±2μm), and 1.3 parts of dispersant (model: BYK-W 9010) were mixed and dispersed at 1050 r / min for 22 min. Then, 118 parts of bisphenol A type liquid epoxy resin, 4.2 parts of KH-560, and 0.45 parts of silicone defoamer (model: BYK-088) were added and stirred for 13 min. Vacuum degassing was carried out at -0.08 MPa for 8.5 min. 29 parts of silane-modified kenaf fiber were added in two batches and stirred for 6 min each time. Then, 152 parts of fused silica powder (particle size ≤45μm) and 642 parts of fused silica sand (20~80 mesh) were added and stirred for 10.5 min. Add 20.5 parts of curing agent (model: HY951) and stir for 3 minutes. Degas under vacuum at -0.08 MPa for 3 minutes. Pour into a mold and vibrate under vacuum at -0.08 MPa for 5 minutes. Then pre-press at 2.5 MPa for 12 minutes. Hold pressure and cure at 61℃ for 62 minutes. Then hold pressure and cure at 76℃ for 95 minutes. Cool, release pressure, demold, and post-cur at 92℃ for 2 hours. After curing, trim the edges, polish with 400-grit and 600-grit sandpaper, remove dust, wash with anhydrous ethanol and dry to obtain an amorphous silicon substrate.
[0051] The bio-antibacterial coating was sprayed onto the surface of an amorphous silicon substrate. The spraying pressure was controlled at 0.22 MPa, the distance between the spray gun and the substrate surface was 16 cm, and the coating amount was 155 g / m². After spraying, the coating was leveled at 25 °C for 22 min, pre-dried at 46 °C for 22 min, and then dried at 56 °C for 32 min. After cooling, the coating was cured at room temperature for 40 h to obtain an amorphous silicon-based bio-antibacterial composite board (the dry film thickness of the bio-antibacterial coating was 55 μm).
[0052] Example 5 4.1 parts of chitosan were added to 390 parts of 1 wt% acetic acid aqueous solution and stirred at 50℃ for 1.8 h to obtain a chitosan solution; 1.40 parts of bamboo leaf flavonoids were added to 92 parts of deionized water and stirred at 49℃ for 14 min, and then slowly added dropwise to the chitosan solution. After the addition was completed, stirring was continued for 28 min to obtain a bamboo leaf flavonoid-chitosan composite solution.
[0053] 5.4 parts of peppermint essential oil and 5.4 parts of Tween 80 were mixed and added dropwise to 129 parts of deionized water under continuous stirring at 1150 r / min and 49℃. After the addition was completed, emulsification was continued for 42 min. The mixture was placed in a 49℃ water bath and bamboo leaf flavonoid-chitosan composite solution was added dropwise under continuous stirring at 1000 r / min. After the addition was completed, the pH of the system was adjusted to 4.1 with 10 wt% citric acid monohydrate aqueous solution and the reaction was carried out for 75 min. Then, 45 parts of 2 wt% sodium tripolyphosphate aqueous solution were added and the reaction was continued for 68 min. After cooling to room temperature and standing for 68 min, the mixture was spray-dried under the conditions of feed rate of 115 mL / h and air inlet temperature of 120℃. The resulting powder was collected, cooled, lightly dispersed and passed through a 150 mesh sieve to obtain bamboo leaf flavonoid-chitosan-coated peppermint essential oil microcapsules.
[0054] Mix 4.9 parts of deionized water with 0.18 parts of dispersant (model: DISPERBYK-190) and stir for 5 minutes. Add 4.5 parts of bamboo leaf flavonoid-chitosan-coated peppermint oil microcapsules in 3 portions and stir for 14 minutes. Add 91 parts of waterborne acrylate-modified polyurethane emulsion (model: EV-6154, solid content 40%±0.5%) and stir for 19 minutes. Then add 0.22 parts of leveling agent (model: BYK-348) and 0.21 parts of waterborne defoamer (model: BYK-024) in sequence and continue stirring for 7 minutes. Let stand to defoam and obtain the bio-antibacterial coating.
[0055] 39 parts of kenaf fiber were cut to a length of 11 mm and then immersed in 670 parts of a 5% sodium hydroxide aqueous solution for 75 min. After washing with deionized water 6 times, the kenaf fiber was vacuum dried at 78 °C for 9.5 h to obtain alkali-treated kenaf fiber. 1.5 parts of KH-560 were added to 310 parts of a 95 vol% ethanol aqueous solution, the pH was adjusted to 4.9 with glacial acetic acid, and the mixture was stirred and pre-hydrolyzed for 38 min. 32 parts of alkali-treated kenaf fiber were then added and immersed for 38 min. The kenaf fiber was then vacuum dried at 78 °C for 5.5 h to obtain silane-modified kenaf fiber.
[0056] 68 parts of bisphenol A type liquid epoxy resin (model: CYD-128), 24 parts of boron carbide (average particle size 9±2μm), and 1.5 parts of dispersant (model: BYK-W 9010) were mixed and dispersed at 1150 r / min for 28 min. Then, 122 parts of bisphenol A type liquid epoxy resin, 4.8 parts of KH-560, and 0.55 parts of silicone defoamer (model: BYK-088) were added and stirred for 15 min. Vacuum degassing was carried out at -0.08 MPa for 9.5 min. 31 parts of silane-modified kenaf fiber were added in three batches and stirred for 7 min each time. Then, 158 parts of fused silica powder (particle size ≤45μm) and 648 parts of fused silica sand (20~80 mesh) were added and stirred for 11.5 min each time. Add 21.5 parts of curing agent (model: HY951) and stir for 4 minutes. Degas under vacuum at -0.08 MPa for 4 minutes. Pour into a mold and vibrate under vacuum at -0.08 MPa for 6 minutes. Pre-press at 2.5 MPa for 14 minutes. Hold pressure and cure at 64℃ for 68 minutes. Hold pressure and cure at 79℃ for 115 minutes. Cool, release pressure, demold, and post-cur at 98℃ for 3 hours. After curing, trim the edges, polish with 400-grit and 600-grit sandpaper, remove dust, wash with anhydrous ethanol and dry to obtain an amorphous silicon substrate.
[0057] The bio-antibacterial coating was sprayed onto the surface of an amorphous silicon substrate. The spraying pressure was controlled at 0.28 MPa, the distance between the spray gun and the substrate surface was 19 cm, and the coating amount was 165 g / m². After spraying, the coating was leveled at 27 °C for 28 min, pre-dried at 49 °C for 28 min, and then dried at 59 °C for 38 min. After cooling, the coating was cured at room temperature for 46 h to obtain an amorphous silicon-based bio-antibacterial composite board (the dry film thickness of the bio-antibacterial coating was 65 μm).
[0058] The thickness of the amorphous silicon substrate obtained in the above embodiments is 15.0±0.5mm.
[0059] The present invention also includes comparative examples and related experiments.
[0060] Comparative Example 1 Compared with Example 1, the only difference is that 1.26 parts of peppermint essential oil were used directly to replace bamboo leaf flavonoid-chitosan to coat peppermint essential oil microcapsules. The other preparation methods and components were completely consistent, and the amorphous silicon-based bio-antibacterial composite board was finally obtained.
[0061] Comparative Example 2 Compared with Example 1, the only difference is that boron carbide was not added when preparing the amorphous silicon substrate. The other preparation methods and components are completely consistent, and the amorphous silicon-based bio-antibacterial composite board is finally obtained.
[0062] Comparative Example 3 Compared with Example 1, the only difference is that silane-modified kenaf fiber was not added when preparing the amorphous silicon substrate. The other preparation methods and components are completely consistent, and the amorphous silicon-based bio-antibacterial composite board is finally obtained.
[0063] Comparative Example 4 Compared with Example 1, the only difference is that natural quartz powder and natural quartz sand are used in equal amounts to replace fused quartz powder and fused quartz sand. The other preparation methods and components are completely consistent, and the amorphous silicon-based bio-antibacterial composite board is finally obtained.
[0064] Performance testing The performance of the amorphous silicon-based antibacterial composite boards prepared in Examples 1-5 and Comparative Examples 1-4 was tested.
[0065] The density and water absorption of each sample were tested according to GB / T35160.1-2017; the compressive strength of each sample was determined according to GB / T35160.3-2017 "Synthetic Stone Test Methods Part 3: Determination of Compressive Strength"; the flexural strength of each sample was determined according to GB / T35160.2-2017 "Synthetic Stone Test Methods Part 2: Determination of Flexural Strength"; the impact resistance of each sample was determined according to GB / T35160.6-2017 "Synthetic Stone Test Methods Part 6: Determination of Impact Resistance"; and the linear coefficient of thermal expansion of each sample was determined according to GB / T35157-2017 "Resin-based Synthetic Stone Slabs" to evaluate the mechanical properties and thermal dimensional stability of the obtained amorphous silicon-based antibacterial composite slab. The test results are shown in Table 1.
[0066] Initial antimicrobial performance testing was conducted according to ASTM E2180-24, "Standard Test Method for Determination of Antimicrobial Activity of Antimicrobial Agents in Polymer or Hydrophobic Materials". A composite board without bamboo leaf flavonoid-chitosan-coated peppermint oil microcapsules and peppermint oil, with other coating components, application amount, and preparation method identical to Example 1, was used as a blank control sample. *Escherichia coli* and *Staphylococcus aureus* were tested separately, with three parallel samples in each group. After 24 hours of incubation, viable bacteria were recovered and counted. The antimicrobial rate was calculated using the following formula: Antibacterial rate / % = (average viable count of blank control sample - average viable count of antibacterial sample) / average viable count of blank control sample × 100%.
[0067] The test results are shown in Table 2.
[0068] To evaluate the durability of the antibacterial effect of amorphous silicon-based bio-antibacterial composite panels after surface scrubbing and thermal aging, accelerated durability treatment was performed on each sample. The specific tests were as follows: The samples were fixed on a reciprocating scrubbing tester, and a non-woven fabric moistened with a 0.5 wt% neutral detergent aqueous solution was used as the scrubbing medium. The samples were scrubbed 1000 times, with one reciprocating cycle counted as one cycle. After scrubbing, the sample surface was rinsed with deionized water and dried at room temperature for 24 hours. Subsequently, the scrubbed samples were placed in a forced-air drying oven at 60±2℃ for 168 hours for accelerated thermal aging, and then equilibrated for 24 hours at 23±2℃ and 50±5% relative humidity. The antibacterial rates against *Escherichia coli* and *Staphylococcus aureus* were determined again according to the initial antibacterial performance test method described above to evaluate the durable antibacterial performance. The test results are shown in Table 3.
[0069] In addition, the initial adhesion of the bio-antibacterial coating on each sample was determined according to GB / T9286-2021 "Cross-cut test for paints and varnishes". After the samples were subjected to durability treatment under the above surface cleaning and accelerated thermal aging conditions, the adhesion of the bio-antibacterial coating was determined again. At the same time, after the durability treatment, the sample surface was observed and the presence of cracking, blistering, peeling, exposure of the substrate, obvious whitening or other abnormal phenomena was recorded to evaluate the bonding stability between the bio-antibacterial coating and the amorphous silicon substrate. The specific test results are shown in Table 4.
[0070] Table 1: Test results of density, water absorption, mechanical properties and thermal dimensional stability.
[0071] As shown in Table 1, the amorphous silicon-based antibacterial composite panels prepared in Examples 1-5 exhibit high compressive strength, flexural strength, and impact resistance, as well as a low coefficient of linear thermal expansion, indicating that the resulting composite panels have a relatively dense internal structure and good mechanical properties and thermal dimensional stability. In Comparative Example 2, without the addition of boron carbide, the sample density decreased, water absorption increased, and compressive strength, flexural strength, and impact resistance all decreased, while the coefficient of linear thermal expansion increased significantly. In Comparative Example 3, without the addition of silane-modified kenaf fiber, water absorption increased, with the most significant decreases in flexural strength and impact resistance. In Comparative Example 4, using natural quartz instead of fused quartz, although the density was higher, the water absorption increased significantly, indicating that the higher density mainly comes from the higher density of the natural quartz aggregate itself and does not directly indicate a denser internal structure. Furthermore, the compressive strength and flexural strength of Comparative Example 4 changed little, but the coefficient of linear thermal expansion increased significantly.
[0072] Table 2: Initial Antibacterial Performance Test Results
[0073] Table 3: Results of Durable Antibacterial Performance Test
[0074] As shown in Table 3, after surface cleaning and accelerated heat aging treatment, the antibacterial rates of Examples 1-5 against Escherichia coli and Staphylococcus aureus still reached over 94.3% and over 93.8%, respectively, indicating that the obtained composite board has good and durable antibacterial properties. In contrast, Comparative Example 1 directly used free peppermint essential oil, and the antibacterial rate decreased significantly after durability treatment.
[0075] Table 4: Results of Adhesion and Appearance Tests for Bio-antibacterial Coating After Durability Treatment
[0076] As shown in Table 4, the initial adhesion of the bio-antibacterial coatings obtained in Examples 1-5 was grade 0, and after durability treatment, the adhesion remained at grade 1. Furthermore, no cracking, blistering, peeling, exposure of the substrate, or significant whitening occurred on the coating surface, indicating that the obtained bio-antibacterial coatings have good adhesion performance and durability stability. Comparative Example 1, which directly used free peppermint essential oil, had an initial adhesion grade of 1, which decreased to grade 2 after durability treatment, and showed slight loss of gloss. In summary, the bio-antibacterial coatings obtained in this invention can maintain good adhesion and appearance integrity even after repeated scrubbing and accelerated heat aging treatment.
[0077] The above are preferred embodiments of the present invention. Those skilled in the art can make several improvements and modifications without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing an amorphous silicon-based bio-antibacterial composite board, characterized in that, Includes the following steps: S1. Deionized water, dispersant, bamboo leaf flavonoid-chitosan-coated peppermint oil microcapsules, water-based acrylate-modified polyurethane emulsion, and additives are mixed and allowed to stand to degas, thus obtaining a bio-antibacterial coating. S2. Mix epoxy resin, boron carbide, dispersant, KH-560 and defoamer and degas under vacuum; then add silane-modified kenaf fiber, fused silica powder and fused silica sand in sequence, add curing agent, stir and degas under vacuum, pour into mold, and after vacuum vibration, pre-pressing and staged heating and pressure curing, cool and demold, then after post-curing, curing, edge trimming, polishing, cleaning and drying, to obtain an amorphous silicon substrate. S3. Apply the bio-antibacterial coating to the surface of the amorphous silicon substrate. After spraying, level, dry, cool and cure to obtain the amorphous silicon-based bio-antibacterial composite board.
2. The method for preparing an amorphous silicon-based bio-antibacterial composite board according to claim 1, characterized in that, The bamboo leaf flavonoid-chitosan-encapsulated peppermint oil microcapsules consist of 5-5.5 parts peppermint oil and 5-5.5 parts Tween. Mix 80 parts and add dropwise to 125-130 parts of deionized water under continuous stirring at 45-50℃ and 1000-1200r / min. After the addition is complete, continue emulsification for 30-45min. Place in a water bath at 45-50℃ and add bamboo leaf flavonoid-chitosan composite solution dropwise under continuous stirring at 1000r / min. After the addition is complete, adjust the pH of the system to 3.8-4.2 with 10wt% citric acid monohydrate aqueous solution and react for 60-80min. Then add 30-50 parts of 2wt% sodium tripolyphosphate aqueous solution and continue the reaction for 60-70min. After cooling to room temperature and standing for 60-70min, spray dry under the conditions of feed rate of 100-120mL / h and air inlet temperature of 120℃. Collect the obtained powder, cool, lightly grind and pass through a 150-mesh sieve.
3. The method for preparing an amorphous silicon-based bio-antibacterial composite board according to claim 2, characterized in that, The bamboo leaf flavonoid-chitosan composite solution is prepared by the following method: 1.25-1.45 parts of bamboo leaf flavonoids are added to 85-95 parts of deionized water and stirred at 45-50°C for 10-15 minutes, then slowly added dropwise to the chitosan solution. After the addition is complete, stirring is continued for 20-30 minutes. The chitosan solution is obtained by adding 3.8-4.2 parts of chitosan to 350-400 parts of 1wt% acetic acid aqueous solution and stirring at 50°C for 1-2 hours.
4. The method for preparing an amorphous silicon-based bio-antibacterial composite board according to claim 1, characterized in that, In step S1, 4.5-5 parts of deionized water and 0.1-0.2 parts of dispersant are mixed and stirred for 3-5 minutes. Then, 3-5 parts of bamboo leaf flavonoid-chitosan-coated peppermint oil microcapsules are added in 2-3 portions and stirred for 10-15 minutes. Next, 87-92 parts of waterborne acrylate-modified polyurethane emulsion are added and mixed and stirred for 15-20 minutes. Then, the additives are added and stirred for another 5-8 minutes. The mixture is allowed to stand and degas to obtain the bio-antibacterial coating. The additives include 0.2 to 0.22 parts of leveling agent and 0.2 to 0.22 parts of water-based defoamer.
5. The method for preparing an amorphous silicon-based bio-antibacterial composite board according to claim 1, characterized in that, The silane-modified kenaf fiber was obtained by adding 1.2-1.6 parts of KH-560 to 280-320 parts of 95 vol% ethanol aqueous solution, adjusting the pH to 4.5-5.0 with glacial acetic acid, stirring and pre-hydrolyzing for 30-40 min, adding 30-32 parts of alkali to treat the kenaf fiber for 30-40 min, and vacuum drying at 70-80℃ for 4-6 h.
6. The method for preparing an amorphous silicon-based bio-antibacterial composite board according to claim 5, characterized in that, The alkali-treated kenaf fiber is obtained by cutting 35-40 parts of kenaf fiber to a length of 8-12 mm, immersing it in 640-680 parts of a 5% sodium hydroxide aqueous solution for 60-80 min, washing it with deionized water 4-6 times, and vacuum drying it at 70-80℃ for 8-10 h.
7. The method for preparing an amorphous silicon-based bio-antibacterial composite board according to claim 1, characterized in that, In step S2, the first part of epoxy resin, boron carbide, and dispersant are mixed and dispersed at 1000-1200 r / min for 20-30 min. Then, the remaining epoxy resin, KH-560, and defoamer are added and mixed for 12-16 min. Vacuum degassing is performed at -0.08 MPa for 8-10 min. Silane-modified kenaf fiber is added in 2-3 batches and mixed for 5-8 min. Then, fused silica powder and fused silica sand are added sequentially and mixed for 10-12 min. Finally, the curing agent is added and mixed for 2-4 minutes. The substrate is degassed under vacuum at -0.08 MPa for 3-4 minutes, then laid into a mold and vibrated under vacuum at -0.08 MPa for 5-6 minutes. It is then pre-pressed at 2.5 MPa for 12-15 minutes, cured under pressure at 60-65℃ for 60-70 minutes, and then cured under pressure at 75-80℃ for 90-120 minutes. After cooling, depressurization, and demolding, it is post-cured at 90-100℃ for 2-3 hours. After curing, edge trimming, polishing, dust removal, washing with anhydrous ethanol, and drying, an amorphous silicon substrate is obtained.
8. The method for preparing an amorphous silicon-based bio-antibacterial composite board according to claim 7, characterized in that, The amount of epoxy resin used in the first part is 60-70 parts, and the amount of epoxy resin used in the remaining part is 115-125 parts; the sanding is done with 400-grit and 600-grit sandpaper; the defoamer is specifically an organosilicon defoamer.
9. The method for preparing an amorphous silicon-based bio-antibacterial composite board according to claim 1, characterized in that, In step S3, the bio-antibacterial coating is sprayed onto the surface of an amorphous silicon substrate. The spraying pressure is controlled at 0.20~0.30MPa, the distance between the spray gun and the substrate surface is 15~20cm, and the coating amount is 150~170g / m². 2 ; After spraying, level at 25~27℃ for 20~30 min, pre-dry at 45~50℃ for 20~30 min, then dry at 55~60℃ for 30~40 min, and after cooling, cure at room temperature for 36~48 h to obtain amorphous silicon-based bio-antibacterial composite board.
10. An amorphous silicon-based bio-antibacterial composite board, characterized in that, The amorphous silicon-based bio-antibacterial composite board is prepared using the preparation method of any one of claims 1 to 9. It comprises an amorphous silicon substrate and a bio-antibacterial coating sprayed onto the surface of the amorphous silicon substrate. The amorphous silicon substrate comprises the following raw materials in parts by weight: 175-195 parts epoxy resin, 20-25 parts boron carbide, 1.2-1.6 parts dispersant, 4-5 parts KH-560, 0.4-0.6 parts defoamer, 28-32 parts silane-modified kenaf fiber, 150-160 parts fused silica powder, 640-650 parts fused silica sand, and 20-22 parts curing agent. The thickness of the amorphous silicon substrate is 14.5-15.5 mm, and the dry film thickness of the bio-antibacterial coating is 50-70 μm.
Citation Information
Patent Citations
Antibacterial and mildew-proof quartz stone and preparation method thereof
CN111875294A